2007
DOI: 10.1111/j.1439-0442.2007.00952.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathology of Udder Lesions in Sows

Abstract: In recent years an increasing frequency of sows with udder lesions has been observed during meat inspection. The frequency and pattern of affected mammary complexes were determined by inspection, palpation, and incision of udders of 640 sows at a local slaughterhouse. From representative lesions, tissue specimens were sampled for histological and bacteriological examination. Moreover, in seven problem cases immunohistochemistry was applied for the identification of Staphylococcus aureus and Arcanobacterium pyo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…ST22 asymptomatic carriage and infections have been reported in companion animals in the UK [29], Ireland [30] and Germany [31], where this clone is prevalent in the human population. The occurrence of EMRSA-15 in companion animals is hypothesized to be a consequence of transmission from humans [4], [29], [32].…”
Section: Discussionmentioning
confidence: 99%
“…ST22 asymptomatic carriage and infections have been reported in companion animals in the UK [29], Ireland [30] and Germany [31], where this clone is prevalent in the human population. The occurrence of EMRSA-15 in companion animals is hypothesized to be a consequence of transmission from humans [4], [29], [32].…”
Section: Discussionmentioning
confidence: 99%
“…These disorders are manifested in reduced litter sizes, hard and long deliveries, delivery of weak piglets, and a lack of desire for mating in boars due to soreness in the extremities. An important issue in pig farming is also the need for early culling of sows from the breeding herd on farms infected with T. pyogenes (Jones and Ward 1989, Christensen et al 2007, Azuma et al 2009). The necessity to cull the sows is mainly associated with the occurrence of lesions in the reproductive system, leading to infertility, embryonic death, abortion, disorders of the menstrual cycle and the resulting lack of heat (Lehnen et al 2006, Hijazin et al 2011.…”
Section: T Pyogenes Infections Of Reproductive Tract In Sowsmentioning
confidence: 99%
“…As a consequence, the malnourished piglets become weak, runted and usually die within the first few days of life (these are "minus variants"). Damage to the mammary gland caused by infection with T. pyogenes also contributes to increased aggressiveness of sows induced by the pain felt during the act of sucking (Waage et al 1999, Christensen et al 2007, Murakami et al 2011. …”
Section: T Pyogenes Infections Of Reproductive Tract In Sowsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, by adopting observation and palpation as their diagnostic method, researchers in Sweden reported that 16% to 19% of sows at 76 farms had granulomatous mastitis in 1999 [4]. In addition, a study performed in Denmark revealed that, at the time of meat inspection, and using inspection and palpation with incision performed if the nature of the lesion was uncertain, 10.5% of slaughterhouse sow carcasses had udder lesions [5].…”
Section: Introductionmentioning
confidence: 99%